2013
DOI: 10.1038/mp.2013.141
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between stressful life events and leukocyte telomere length is associated with PTSD

Abstract: hippocampus of schizophrenia patients in post-mortem studies. 5 Furthermore, DISC1 has previously been shown to directly regulate the GSK3ß signalling pathway with downstream effects on neurogenesis. 6 NRG1-ErbB signalling is also known to interact with the Wnt-GSK3ß signalling pathway, 4 and genetic variants altering NRG1 expression have been implicated in a range of neuropsychiatric disorders. 3 Recently Makinodan et al. 7 have shown that prolonged social isolation in mice during the juvenile period (PN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 10 publications
1
49
3
Order By: Relevance
“…Previous cross sectional studies in PTSD have suggested an association with decreased telomere length (Ladwig et al 2013;Malan et al 2011;O'Donovan et al 2011) although sometimes only in interaction with pre--existent youth trauma (Zhang et al 2013). Although the relationship of the two aging parameters with PTSD is in the opposite direction as previously reported, these findings are not without precedent.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous cross sectional studies in PTSD have suggested an association with decreased telomere length (Ladwig et al 2013;Malan et al 2011;O'Donovan et al 2011) although sometimes only in interaction with pre--existent youth trauma (Zhang et al 2013). Although the relationship of the two aging parameters with PTSD is in the opposite direction as previously reported, these findings are not without precedent.…”
Section: Discussioncontrasting
confidence: 52%
“…One study found significantly shorter LTL in PTSD, but found that this effect was largely explained by early life stress, which is a risk factor for developing PTSD (O'Donovan et al, 2011a). In another study, involving combat deployed soldiers, individuals with PTSD had significantly shorter LTL compared to combat-deployed soldiers without PTSD (Zhang et al, 2014). That study did not detect a relationship between early life trauma and LTL, although the childhood trauma measure used was brief and non-validated.…”
Section: Telomere Length In Psychiatric Illnessesmentioning
confidence: 99%
“…Reduced telomere length has also been documented in MDD (10, 4044), although some studies have been negative (45, 46). A few investigations also found reduced leukocyte telomere length in anxiety disorders (45, 47), post-traumatic stress disorder (PTSD) (4851), bipolar II disorder (52), schizophrenia (53), and substance use disorders (54, 55). Chronicity of MDD is linked to leukocyte telomere shortening (43, 47, 56), suggesting that loss of telomere length may be a consequence of other aspects of the disease process.…”
Section: Introductionmentioning
confidence: 99%